Biologically Synthesized Peptides Show Remarkable Inhibition Activity against Angiotensin-Converting Enzyme: A Promising Approach for Peptide Development against Autoimmune Diseases. (20th June 2022) - Mujtaba, Nosheen; Jahan, Nazish; Jamal, Adil; Abrar, Shazia; Kiran, Shumaila; Rasool, Atizaz; Hossain, Md Belal; Bahwerth, Fayez Saeed; Nomani, Ibtesam; Iqbal, Khalid Javed
Abstract : Angiotensin-converting enzyme (ACE) regulates several biological functions besides its vital role in immune functions. ACE is elevated in immune cells in inflammatory diseases including atherosclerosis, granuloma, chronic kidney disease, and also autoimmune diseases, like multiple sclerosis, rheumatoid arthritis, and type I diabetes. No significant information prevails in the literature regarding the isolation, identification, and profiling of potential ACE inhibitory peptides. In the present study, indigenous crop varieties like seeds (peanut, corn, oat, sunflower, chickpea, parsley, cottonseed, papaya, sesame, and flaxseed) were used to evaluate their ACE inhibition activity. Variables including hydrolysis time, enzyme-to-substrate ratio (E/S), pH, and temperature were standardized to acquire the most suitable and optimum ACE inhibition activity. Seeds of cotton, chickpea, and peanuts displayed remarkably maximum ACE inhibition activity than other plants. The study disclosed that maximum ACE inhibitory activity (86%) was evaluated from cottonseed at pH 8.0, temperature of 45°C, hydrolysis time of 2 hrs, and enzyme to the substrate (E/S) ratio of 1 : 5 followed by peanuts (76%) and chickpea (55%). SDS-PAGE confirmed that vicilin protein is present in cottonseed and peanut seed while cruciferin and napin proteins are present in chickpeas. LC-MS/MS analysis disclosed potential novel peptides in hydrolyzed cottonseed that can be ascribed as potential ACE inhibitors which have never been reported and studied earlier. The current study further showed that cottonseed peptides due to their promising ACE inhibitory activity can be a valuable source in the field of ACE inhibitor development.